Exploring the Influence of Music on Student Consumptive Behavior: A Mixed-Methods Study - Bagus Hidayat; Widya Fitri Aryani (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This research explores the influence of music on student consumptive behavior, focusing on the role of music preferences, mood, and purchasing decisions. A mixed-methods approach was employed, combining quantitative survey data with qualitative insights from interviews and focus groups. The survey revealed that students' genre preferences were positively correlated with their shopping behavior, suggesting that the type of music they listen to may influence their purchasing decisions. Additionally, students who reported feeling happier and more relaxed while shopping were more likely to make impulsive purchases and spend more money, suggesting that mood may influence students' spending habits. The qualitative data provided deeper insights into the emotional connection students have with music and how it influences their perceptions of products. Overall, the findings suggest that music plays a significant role in shaping students' shopping experiences and consumer behavior, with practical implications for marketers, retailers, and educators.